ANALISIS IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PENINGKATAN KEMANDIRIAN BELAJAR SISWA KELAS V DI SD NEGERI 1 ADIKARSO TAHUN AJARAN 2020/2021 - Fadli Syahrizal; Suhartono Suhartono; Rokhmaniyah Rokhmaniyah (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2022)
AbstractThe study aimed to describe the implementation of character education in improving the independence in learning to fifth grade students of SD Negeri 1 Adikarso in academic year of 2020/2021. It was a qualitative study method with a case study approach. The results indicated that: first, the implementation of character education in improving the independence in learning to fifth grade students of SD Negeri 1 Adikarso ran well. Second, the implication of character education in improving the independence in learning to fifth grade students of SD Negeri 1 Adikarso had been carried out well by the majority of students. Third, there were obstacles and efforts in the implementation of character education in improving the independence in learning to fifth grade students of SD Negeri 1 Adikarso. It concludes that the implementation of character education in improving the independence in learning to fifth grade students of SD Negeri 1 Adikarso works well. The implementation of character education finds obstacles but those have been handled by the teacher.  Keywords: Implementation, character education, independence in learning